Perspectives on ethnic and racial disparities in Alzheimer's disease and related dementias: Update and areas of immediate need. Issue 2 (13th December 2018) - Babulal, Ganesh M.; Quiroz, Yakeel T.; Albensi, Benedict C.; Arenaza‐Urquijo, Eider; Astell, Arlene J.; Babiloni, Claudio; Bahar‐Fuchs, Alex; Bell, Joanne; Bowman, Gene L.; Brickman, Adam M.; Chételat, Gaël; Ciro, Carrie; et al.
Abstract: Alzheimer's disease and related dementias (ADRDs) are a global crisis facing the aging population and society as a whole. With the numbers of people with ADRDs predicted to rise dramatically across the world, the scientific community can no longer neglect the need for research focusing on ADRDs among underrepresented ethnoracial diverse groups. The Alzheimer's Association International Society to Advance Alzheimer's Research and Treatment (ISTAART; alz.org/ISTAART ) comprises a number of professional interest areas (PIAs), each focusing on a major scientific area associated with ADRDs. We leverage the expertise of the existing international cadre of ISTAART scientists and experts to synthesize a cross‐PIA white paper that provides both a concise "state‐of‐the‐science" report of ethnoracial factors across PIA foci and updated recommendations to address immediate needs to advance ADRD science across ethnoracial populations.